NRF2 activation by antioxidant antidiabetic agents accelerates tumor metastasis - Wang, Hui; Liu, Xiufei; Long, Min; Huang, Yi; Zhang, Linlin; Zhang, Rui; Zheng, Yi; Liao, Xiaoyu; Wang, Yuren; Liao, Qian; Li, Wenjie; Tang, Zili; et al. (Science translational medicine, 2016)
Adding fuel to a cancer fire - Diabetic patients are at increased risk of developing cancer. Some risks of antioxidant drugs in the setting of cancer are already known, and now, Wang et al. show that diabetic drugs with antioxidant properties may cause problems as well. The authors evaluated several antidiabetic drugs such as saxagliptin and sitagliptin, as well as α-lipoic acid, a supplement used to treat diabetic neuropathy. All of these compounds have antioxidant properties, and all accelerated metastasis in mouse models of cancer. It remains to be determined whether these findings will hold up in human patients, but it may be best to exercise caution when giving antioxidant drugs to patients at increased risk for cancer. - Cancer is a common comorbidity of diabetic patients; however, little is known about the effects that antidiabetic drugs have on tumors. We discovered that common classes of drugs used in type 2 diabetes mellitus, the hypoglycemic dipeptidyl peptidase-4 inhibitors (DPP-4i) saxagliptin and sitagliptin, as well as the antineuropathic α-lipoic acid (ALA), do not increase tumor incidence but increase the risk of metastasis of existing tumors. Specifically, these drugs induce prolonged activation of the nuclear factor E2-related factor 2 (NRF2)-mediated antioxidant response through inhibition of KEAP1-C151-dependent ubiquitination and subsequent degradation of NRF2, resulting in up-regulated expression of metastasis-associated proteins, increased cancer cell migration, and promotion of metastasis in xenograft mouse models. Accordingly, knockdown of NRF2 attenuated naturally occurring and DPP-4i-induced tumor metastasis, whereas NRF2 activation accelerated metastasis. Furthermore, in human liver cancer tissue samples, increased NRF2 expression correlated with metastasis. Our findings suggest that antioxidants that activate NRF2 signaling may need to be administered with caution in cancer patients, such as diabetic patients with cancer. Moreover, NRF2 may be a potential biomarker and therapeutic target for tumor metastasis. - Antioxidant antidiabetic drugs may promote tumor metastasis. - Antioxidant antidiabetic drugs may promote tumor metastasis.
Gesehen am 05.06.2020